(untitled) (Colloquia Comparativa Litterarum, 2025)
The Stepford Wives, a novel by Ira Levin published in 1972, describes a micro-dystopian society, which imposes a strict ‘traditional’ order, by transforming women into compliant wives programmed to serve their husbands. The book has been adapted to screen several times. The present paper will focus on a comparison between the original literary work and the first adaptation of 1975 by British director Bryan Forbes, seen through the notions of genre, gender, class and race.